Cytotoxic effects of bromelain in human gastrointestinal carcinoma cell lines (MKN45, KATO-III, HT29-5F12, and HT29-5M21) - Amini, Afshin (Dove Medical Press, 2013)
BACKGROUND: Bromelain is a pineapple stem extract with a variety of therapeutic benefits arising from interaction with a number of different biological processes. Several preclinical studies and anecdotal clinical observations have reported the anticancer properties of bromelain. In the present study, we investigated the cytotoxic effects of bromelain in four human cancer cell lines of gastrointestinal origin and the mechanisms involved. METHODS: The gastric carcinoma cell lines (KATO-III and MKN45) and two chemoresistant subpopulations of the HT29 colon adenocarcinoma cell line (HT29-5M21 and HT29-5F12) were treated with a range of concentrations of bromelain, as well as with cisplatin as a positive control. The effect of bromelain on the growth and proliferation of cancer cells was determined using a sulforhodamine B assay after 72 hours of treatment. Expression of apoptosis-associated proteins in MKN45 cells treated with bromelain was analyzed by Western blotting. RESULTS: Data from our sulforhodamine B assay showed that bromelain inhibited proliferation of HT29-5F12, HT29-5M21, MKN45, and KATO-III cells, with respective half maximal inhibitory concentration values of 29, 34, 94, and 142 μg/mL. Analyzing the expression of proapoptotic and antiapoptotic proteins in bromelain-treated MKN45 cells, we observed activation of the caspase system, cleavage of PARP and p53, overexpression of cytochrome C, attenuation of phospho-Akt and Bcl2, and removal of MUC1. Apart from the caspase-dependent apoptosis observed, emergence of cleaved p53 supports a direct, extranuclear apoptotic function of p53. Moreover, interrupted Akt signaling and attenuation of Bcl2 and MUC1 oncoproteins suggest impaired survival of cancer cells. CONCLUSION: Our findings collectively indicate that bromelain exerts cytotoxic effects in a panel of human gastric and colon carcinoma cells. Our study of MKN45 cells implicated different mechanisms in bromelain-induced cell death. While promoting apoptosis with involvement of the caspase system and extranuclear p53, bromelain also appears to impair cancer cell survival by blocking the Akt pathway and attenuating Bcl2 and MUC1 oncoproteins.